2015
DOI: 10.1021/ef502682v
|View full text |Cite
|
Sign up to set email alerts
|

Desulfurization Performance of Ether-Functionalized Imidazolium-Based Ionic Liquids Supported on Porous Silica Gel

Abstract: Ether-functionalized imidazolium-based ionic liquids (EFIILs) [C 3 O 1 Mim][H 3 CSO 3 ], [C 5 O 2 Mim][H 3 CSO 3 ], and [C 7 O 3 Mim][H 3 CSO 3 ] were supported onto porous silica gel particles via a facile impregnation method. The synthesized EFIILs/SiO 2 were characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and Brunauer−Emmett−Teller (BET). Results show that the EFIILs/SiO 2 have good thermal stability, high porosity, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…A few years ago, Xun et al reported on ionic liquid catalysts ([Bmim]FeCl 4 ) embedded in silica gel, and various conditions were investigated for the removal of DBT using the catalytic oxidative desulfurization process, where the desulfurization efficiency was over 90%, even after recycling the catalyst six times [ 159 ]. This study marked a new era for the emergence of ionic liquid supported silica gels and interesting examples were reported by Zhao et al and Safa et al The former study reported on using ether functionalized ionic liquid/silica gel catalysts to adsorb SO 2 and the adsorption capacities ranged from 2.621 mol of SO 2 /mol for [C 3 O 1 Mim][H 3 CSO 3 ] to 3.453 mol of SO 2 /mol for [C 7 O 3 Mim][H 3 CSO 3 ], indicating an increase in adsorption capacity with elongation in chain length of the cation [ 160 ]. The latter study reported on using 1-octyl-3-methylimidazolium hydrogen sulfate ([Omim][HSO 4] ) in the silica-gel matrix for ODS of a model oil composed of DBT and real diesel fuel.…”
Section: Mesoporous Silica and Mesoporous Silica Nanoparticles In mentioning
confidence: 99%
See 1 more Smart Citation
“…A few years ago, Xun et al reported on ionic liquid catalysts ([Bmim]FeCl 4 ) embedded in silica gel, and various conditions were investigated for the removal of DBT using the catalytic oxidative desulfurization process, where the desulfurization efficiency was over 90%, even after recycling the catalyst six times [ 159 ]. This study marked a new era for the emergence of ionic liquid supported silica gels and interesting examples were reported by Zhao et al and Safa et al The former study reported on using ether functionalized ionic liquid/silica gel catalysts to adsorb SO 2 and the adsorption capacities ranged from 2.621 mol of SO 2 /mol for [C 3 O 1 Mim][H 3 CSO 3 ] to 3.453 mol of SO 2 /mol for [C 7 O 3 Mim][H 3 CSO 3 ], indicating an increase in adsorption capacity with elongation in chain length of the cation [ 160 ]. The latter study reported on using 1-octyl-3-methylimidazolium hydrogen sulfate ([Omim][HSO 4] ) in the silica-gel matrix for ODS of a model oil composed of DBT and real diesel fuel.…”
Section: Mesoporous Silica and Mesoporous Silica Nanoparticles In mentioning
confidence: 99%
“…These studies indicate direct interactions of HOMO orbitals with the LUMO (lowest unoccupied molecular orbital), belonging to the active species present in silica gel, are responsible for selective elimination of sulfur rich molecules in fuel. Wang et al reported on Ni-heteropolyacids supported on silica gel and used them for removal of thiophene, alkyl thiophene, BT, and DBT under Ultrasound and Ultraviolet irradiation conditions [157] [160]. The latter study reported on using 1-octyl-3-methylimidazolium hydrogen sulfate ([Omim][HSO 4] ) in the silica-gel matrix for ODS of a model oil composed of DBT and real diesel fuel.…”
Section: Silica Gelsmentioning
confidence: 99%
“…Because of the importance of SO 2 in CO 2 capture, there are a lot of investigations of the impact of SO 2 on CO 2 capture properties of zeolites, , solid amine sorbents, and supported ionic liquid-phase (SILP) materials. SO 2 impurities have been proved to bind irreversibly to most amine groups that lead to sorbent poisoning. As an example for solid amine sorbents, Rezaei and Jones , have quantified the SO 2 adsorption capacities of a series-supported amine adsorbents and researched the effects of SO 2 on CO 2 capture performance.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16] Nevertheless, their adsorption capacities, selectivities, and desulfurization kinetics significantly restrain their real application in industry. [17][18][19] Recently, remarkable progress on ADS have been achieved by using metal-organic frameworks (MOFs) based adsorbents, for example, vanadium benzenedicarboxylate (MIL-47), 20,21 chromium benzenedicarboxylate (MIL-101), 22 and HKUST-1 (MOF-199). 23,24 However, the drawbacks of MOFs adsorbents, such as their limited stabilities and challenging synthetic conditions, have yet to make them feasible for large-scale industrial fabrication.…”
Section: Introductionmentioning
confidence: 99%